Correction to: Fault detection in distillation column using NARX neural network (Neural Computing and Applications, (2020), 32, 8, (3503-3519), 10.1007/s00521-018-3658-z) - Taqvi, S.A. (Springer Science and Business Media Deutschland GmbH, 2022)
The original version of this article contained errors in the affiliation list. We found that the second affiliation of 1st Author ââSyed A. Taqviââ is missing. The missed affiliation is given below: Syed A. Taqvi1,21Chemical Engineering Department, Universiti Teknologi PETRONAS, 32610 Seri Iskandar, Perak Darul Ridzuan, Malaysia 2Department of Chemical Engineering, NED University of Engineering and Technology Karachi, 75270, Pakistan. These errors have now been corrected in the HTML and PDF versions of the Article. Â© 2021, Springer-Verlag London Ltd., part of Springer Nature.